NEUROLOGIC COMPLICATION IN LUNG ADENOCARCINOMA EFGR MUTATION WITH A CONSOLIDATION-TO-TUMOR-RATIO (CTR) >75% - Prasetyo, Firman Adi; Sensusiati, Anggraini Dwi (International Journal of Radiology and Imaging, 2023)
Lung adenocarcinoma (LAC) accounts for a large proportion of lung cancer subtypes and causes various neurologic complications. This calls for extensive use of CT scans for detecting lung cancer which contains ground glass opacity (GGO). A Consolidation-to-tumor-ratio (CTR) >75% has a worse prognosis in LAC. A male 50-years-old came with paraplegia, complaining suddenly that his legs could not be moved. The patient performed a spine MRI with the result indicating a spinal metastatic process. Furthermore, the Chest X-ray only showed consolidation in the right paracardial area but the chest CT confirmed as lung mass followed by histopathology examination result of LAC with EFGR mutation. After three months, the patient also had multiple cerebral infarcts. We reported one case of LAC EFGR mutation with a CTR of 83%. higher CTR has more invasive adenocarcinomas and also correlated with immunosuppressive conditions compared with a low CTR. The patient was diagnosed lately after a complication of spinal compression. The other neurological complication is multiple cerebral infarcts. The pathogenesis of cancer-associated stroke has not been fully clarified. The pathophysiological mechanisms of these cerebrovascular complications are multifactorial. Other biological markers may also be of interest, including high levels of C-reactive protein (CRP), high levels of fibrinogen, decreased hemoglobin, and hypoalbuminemia. Retrospective studies on acute stroke detected significantly higher levels of fibrinogen and CRP in patients with cryptogenic stroke and occult malignancy. LAC with a CTR >75% is more invasive due to neurologic complications such as spinal metastases and stroke infarction. Keywords: Lung adenocarcinoma, CTR, Stroke, Metastase